Effects of vitamin A on intramuscular fat development in beef cattle: A meta-analysis - Li, Wei; Wang, Fang; Sun, Fang; Qu, Yongli; Liu, Chunhai; Han, Yongsheng; Wang, Hongbao; Jiang, Botao; Zhong, Peng; Wang, Jiahui; Song, Xueying; Huang, Meng; et al. (Frontiers in Veterinary Science, 2023)
Vitamin A, a fat-soluble vitamin, is the basic substance required to maintain healthy vision and the main physiological functions of cattle. The results from previous studies regarding the effect of vitamin A on intramuscular fat varied. This meta-analysis aimed to generate a more comprehensive understanding of the relationship between vitamin A and intramuscular fat content and to provide potential clues for future research and commercial practice. Electronic databases such as MEDLINE and Ovid were systematically searched, and studies investigating the relationship between vitamin A and intramuscular fat content were included. Standardized mean differences (SMDs) in intramuscular fat percentage and intramuscular fat score, with their respective 95% confidence intervals (CIs), were calculated. The heterogeneity and publication bias were evaluated. A total of 152 articles were identified through searches of databases. Seven articles were confirmed for inclusion in this meta-analysis. The SMD of IMF percentage derived from the analysis was−0.78 (-2.68, 1.12) (Q = 246.84, p < 0.01). The SMD of the IMF score was 1.25 (-2.75, 5.25) (Q = 87.20, p < 0.01). Our meta-analysis indicates that the addition of vitamin A could decrease intramuscular fat in cattle steers.